Pengaruh Current Ratio Dan Debt To Asset Ratio Terhadap Return On Asset Pada PT Semen Batu Raja Tbk Periode 2014 – 2023 - Nhurul Fatmawati; Sutiman Sutiman (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The massive development of infrastructure and property that occurs also increases the need for cement products as one of the supports for development. The large number of requests can create industry competition which can later affect company finances. This study aims to analyze the partial and simultaneous influence between Current Ratio and Debt To Asset Ratio which has an impact on Return On Asset of PT Semen Baturaja Tbk for the period 2014-2023. The method used in this research is quantitative method. The population in this study were all financial statements of PT Semen Beturaja Tbk for the period 2014-2023. the analysis method used is descriptive statistical analysis, classical assumption test, multiple linear analysis and simple linear analysis. hypothesis testing using F-test, t-test and determination which is assisted using the IMB SPSS Statistics 29 program. The results showed that the Current Ratio partially had a positive and significant effect on Return On Asset, Debt to Asset Ratio partially had no significant effect on Return On Asset, and simultaneously, the Current Ratio and Debt to Asset Ratio had a significant effect on Return On Asset